Introduction to Design and Analysis of Torsional Vibration Dampers in Vehicle Industry - Venczel, Márk; Veress, Árpád (International Journal of Engineering and Management Sciences, 2019)
The crankshaft of today’s internal combustion engines with high performance output are exposed to harmful torsional oscillations originated from the unbalanced gas and inertial forces. To avoid the fatigue damage of engine components, caused by the undesired vibrations, torsional vibration dampers can be applied. Viscodampers are one type of the torsional vibration dampers, which operational fluid is silicone oil. For cost-effective R&D activities and production, finite element and finite volume numerical discretization methods based calculation techniques must be involved into the engineering work supported by the modern computer technology. The aim of this paper is to provide an insight into the multidisciplinary design and development process of visco-dampers in vehicle industry applications. Four different examples as structural, fatigue, CFD analyses and structural optimization have been introduced in the present work. It turned out from the static structural and fatigue analyses, that the investigated damper has safety factor over the limit for both static structural and fatigue analyses, so it is suitable for the given load conditions. In the structural optimization process 34.36% mass reduction has been achieved. According to the coupled fluid dynamic and heat transfer simulations a rather stagnating air zone evolved between the engine and the damper during the operation, which can cause efficiency reduction of cooling fins mounted onto the housing. In light of the numerical results, the suitable damper position has been determined for the highest heat transfer.